Modeling and numerical simulations of transport mechanism in microplar fluid using microstructures and nonlinear porous medium theories: An analysis related to energy and sustainability - Salmi, Abdelatif; Nawaz, M. (Journal of thermal analysis and calorimetry, 2025)
In this study, the simultaneous transport of heat and mass subjected to fluid–structure interaction in Darcy–Forchheimer porous media is modeled with the help of conservation laws of mass, linear and angular momentum, and energy. The modeled equations are solved numerically using the Galerkin finite element method. The solutions are checked for their convergence and accuracy. The magnetic field is responsible for the increase in stress on the wall. Therefore, if stress on the surface is needed to decrease, then a magnetic field should not be applied to the flow. However, if stress is required for any engineering process like spray coating, then magnetic fields are a favorable factor. Couple stress associated with nanofluids has the highest magnitude in comparison with. The couple stress tends to increase as a function of vortex viscosity, considered fluids. Couple stress also increases with an increase in the intensity of the magnetic field. Angular velocity gradient in case of A l 2 O 3 + S i C + M o S 2 + E G are the highest relative to A l 2 O 3 + E G and A l 2 O 3 + S i C + E G . The presence of the progress media is responsible for an increase in wall shear stress on the surface. Thus, porous media is a favorable agent if the stress on the surface is required to increase, whereas it is unwanted if the stress on the surface is needed to reduce. The Forchheimer porous medium is more effective than the Darcy porous medium in controlling the viscous region. However, Forchheimer porous medium causes an enhancement in shear stress, which is not required in some systems as extra wall shear stress may cause damage to the system.